Distribution and comparative genomic analysis of antimicrobial gene clusters found in Pantoea - Kirk, Ashlyn; Stavrinides, John (Frontiers in Microbiology, 2024)
Members of the bacterial genus Pantoea produce a variety of antimicrobial products that are effective against plant, animal, and human pathogens. To date, little is known about the distribution and evolutionary history of these clusters. We surveyed the public databases for the 12 currently known antibiotic biosynthetic gene clusters found across Pantoea strains to determine their distribution. We show that some clusters, namely pantocin B, PNP-3, and PNP-4 are found strictly in Pantoea, while agglomerin, andrimid, AGA, dapdiamide, herbicolin, PNP-1, PNP-2, PNP-5, and pantocin A, are more broadly distributed in distantly related genera within Vibrionaceae, Pectobacteriaceae, Yersiniaceae, Morganellaceae, and Hafniaceae. We evaluated the evolutionary history of these gene clusters relative to a cpn60-based species tree, considering the flanking regions of each cluster, %GC, and presence of mobile genetic elements, and identified potential occurrences of horizontal gene transfer. Lastly, we also describe the biosynthetic gene cluster of pantocin B in the strain Pantoea agglomerans Eh318 more than 20 years after this antibiotic was first described.